The 2D scattering problem solution on a body in homogeneous medium via the method of nonlocal boundary condition - Шульга, С. Н.; Багацкая, О. В.; Стрижаченко, А. В. (Visnyk of V.N. Karazin Kharkiv National University, series “Radio Physics and Electronics”, 1970)
The 2D scattering problem for E -polarized wave on a dielectric inclusion in homogeneous medium is considered via the method of nonlocal boundary conditions. The nonlocal boundary condition on the circuit of the inclusion is obtained by the theory of the logarithmic potential of a double layer. The closed boundary value problem for the definition of the field inside the inclusion and scattered field is formulated.